The clinical efficacy of herbal medicines containing leeches in the treatment of coronary heart disease: a systematic review and meta-analysis - Ziyuan, Zhao; Di, Ye; Mei, Liang; Yujing, Jin; Jinghui, Zheng (Frontiers in Pharmacology, 2025)
BackgroundCoronary heart disease (CHD) is a leading global cause of mortality, contributing to angina, arrhythmia, myocardial infarction, heart failure, and sudden death. Traditional treatments, including antiplatelet drugs, statins, β-blockers, and coronary stents, have notable side effects such as gastrointestinal bleeding and liver or muscle dysfunction, with post-operative stent complications. Recent studies have identified bioactive substances in leeches, particularly the natural anticoagulant hirudin, which inhibits thrombin and may help mitigate complications of coronary artery disease. Hirudin inhibits thrombin, reduces platelet aggregation, and lowers thrombosis risk. This meta-analysis evaluates the clinical efficacy and safety of Chinese herbal medicines containing leech in treating CHD, focusing on cardiovascular outcomes and adverse events.MethodsA systematic search of databases including PubMed, EMBASE, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), WanFang Data (Wanfang), and VIP China Science and Technology Journal Database (VIP) was conducted to identify randomized controlled trials (RCTs) involving leech-containing Chinese herbal medicines for CHD patients up until February 2025. Key efficacy outcomes analyzed were total effective rate, ECG efficacy, and hemorheological parameters, while adverse event rates assessed treatment safety. The meta-analysis used Standardized Mean Difference (SMD) and 95% confidence intervals (CI) to assess efficacy, and Odds Ratio (OR) with 95% CI for safety. Subgroup analyses examined the relationship between therapeutic effects and patient characteristics.ResultsSixty-five studies involving 7,221 patients were included. The results showed that leech-based treatments significantly improved the total effective rate [OR = 3.70, 95% CI (3.19, 4.31), Z = 17.05, P < 0.00001] and ECG efficacy [OR = 2.58, 95% CI (2.23, 2.99), P < 0.0001], along with significant improvements in hemorheological parameters. Subgroup analysis indicated leech treatments were particularly effective for improving the total effective rate, ECG outcomes, and hemorheological indices. Importantly, adverse event rates did not increase compared to conventional treatments.ConclusionChinese herbal medicines containing leeches provide significant clinical benefits for CHD, particularly in improving ECG outcomes and blood parameters. These findings suggest that leech-based treatments are both effective and safe, with no increase in adverse events.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, Identifier CRD42024564675.